SERVICE LEARNING DI KB RAUDLATUT THOLIBIN BULUPITU GONDANGLEGI-MALANG (Studi Kasus Pembelajaran Untuk Anak Usia Kelompok B) - Lista Aimil; Nikmahtul Khoir Tri Yulia (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2023)
Learning (Service Learning) is an approach that provides a practical application, new knowledge and skills to the needs of the community to develop the quality of learning for students. This study aims to describe the Service Learning process at KB Raudlatut Tholibin Bulupitu Gondanglegi-Malang. The qualitative research method is to understand what cases are experienced by the research subject holistically. Indicators developed in the form of curriculum implementation, developing learning strategies and learning management. The service learning process includes (1) the teacher must make the learning process as interesting as possible, (2) the messages conveyed through learning must be interesting, clear and real, (3) foster motivation to learn, (4) let children learn according to their interests. The strategy for the process of implementing Service Lerning is based on the awareness as an educator that it emphasizes teachers and school members complying with learning norms with discipline, guiding and directing to solve work problems, willing to provide assistance in a proportionate and professional manner. Suggestions related to teacher competence that the competence of teachers in this institution still needs to be improved.